1982
DOI: 10.1111/j.1471-0528.1982.tb04651.x
|View full text |Cite
|
Sign up to set email alerts
|

Relation between the luteinizing hormone peak, the nadir of the basal body temperature and the cervical mucus score

Abstract: The results of a cervical mucus scoring system and of basal body temperature (BBT) chart interpretation were compared with those of a short-incubation radioimmunoassay for luteinizing hormone (LH) in 198 ovulatory menstrual cycles. The timing of the maximal cervical mucus score was similar to that of the LH peak in all but 7% of assessable cycles. In contrast, the timing of the nadir of the BBT differed widely from that of the LH peak in 45% of cycles with interpretable charts. These findings suggest that cerv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
1

Year Published

1984
1984
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 11 publications
(6 reference statements)
0
23
0
1
Order By: Relevance
“…for the Determination of the Fertile Period 1983) was 13.5 (SD 2.8) days and in the present study (using the LH peak as a marker) the luteal phase was found to last 14.13 days (SD 1.41 days). It is difficult to compare these observations since the time of the LH peak correlates with the day of maximum cervical mucus in only 44% of subjects (Templeton et al 1982). However, the relationship between the LH peak and ovulation has been defined (WHO Task Force on Methods for the Determination of the Fertile Period 1980).…”
Section: Discussionmentioning
confidence: 99%
“…for the Determination of the Fertile Period 1983) was 13.5 (SD 2.8) days and in the present study (using the LH peak as a marker) the luteal phase was found to last 14.13 days (SD 1.41 days). It is difficult to compare these observations since the time of the LH peak correlates with the day of maximum cervical mucus in only 44% of subjects (Templeton et al 1982). However, the relationship between the LH peak and ovulation has been defined (WHO Task Force on Methods for the Determination of the Fertile Period 1980).…”
Section: Discussionmentioning
confidence: 99%
“…These data are known to be rather unreliable for predicting optimal conditions of the cervical mucus (Nulsen et al 1987). More reliable methods, such as follicle measurement by ultrasound and urinary LH or serum oestradiol determinations (Templeton et al 1982; Vermesh et al 1987; Hamilton et al 1986), are used by only 37% of the responding gynaecologists.…”
Section: Discussionmentioning
confidence: 99%
“…Together with the menstrual calenders, these measurements provide a comprehensive and complete evaluation of the menstrual cycle that could not be obtained by other means. Clearly, a direct quantification of ovarian steroid excretion patterns, as done in this study (1) and the two previous studies (2, 3), provides a more direct and objective evaluation of both follicular and luteal phase ovarian hormone production than do BBT shift patterns (7)(8)(9)(10)(11). While BBT shifts may be somewhat accurate in identifying abnormal luteal phases, it is not clear that BBT clearly identifies the relative normality of the follicular and luteal phases of the menstrual cycle (7)(8)(9)(10)(11).…”
Section: Et Al (3)mentioning
confidence: 99%
“…Clearly, a direct quantification of ovarian steroid excretion patterns, as done in this study (1) and the two previous studies (2, 3), provides a more direct and objective evaluation of both follicular and luteal phase ovarian hormone production than do BBT shift patterns (7)(8)(9)(10)(11). While BBT shifts may be somewhat accurate in identifying abnormal luteal phases, it is not clear that BBT clearly identifies the relative normality of the follicular and luteal phases of the menstrual cycle (7)(8)(9)(10)(11). In fact, BBT is limited to detecting only luteal phase hormone changes and provides little, if any, information regarding absolute hormone production in the follicular phase or the luteal phase (7-11).…”
Section: Et Al (3)mentioning
confidence: 99%
See 1 more Smart Citation